Rewriting this <span>7-y=5x+11 in standard form involves only changing the order in which the terms appear:
</span><span>7-y=5x+11 becomes 5x + y + 11 - 7 = 0, or 5x + y + 4 = 0, or 5x + y = -4.</span>
-2 because you have to reduce
That would be the area of a circle of radius 12 miles
= pi r^2 = 452.4 square miles to nearest tenth.
Answer:
3(x + 2)(2x - 5)
Step-by-step explanation:
Given
6x² - 3x - 30 ← factor out 3 from each term
= 3(2x² - x - 10) ← factor the quadratic
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 2 × - 10 = - 20 and sum = - 1
The factors are + 4 and - 5
Use these factors to split the x- term
2x² + 4x - 5x - 10 ( factor the first/second and third/fourth terms )
= 2x(x + 2) - 5(x + 2) ← factor out (x + 2) from each term
= (x + 2)(2x - 5), thus
2x² - x - 10 = (x + 2)(2x - 5) and
6x² - 3x - 30
= 3(x + 2)(2x - 5) ← in factored form